Lower limbs amputation and physiotherapy rehabilitation at the National Authority for Prosthetics and Orthotics, Sudan - Faiza Hussein; Nusaiba Omer; Wafaa Shargawi; Hassan Abdelnour (Ananda - Health & Education Foundation, 2026)
Background: Each year, approximately 150,000 individuals in the United States undergo lower extremity amputations. In Sudan, a range of rehabilitation services for amputation patients is offered through organizations in both governmental and public sectors. The National Authority for Prosthetics and Orthotics (NAPO) adopts a multidisciplinary rehabilitation approach to help amputation patients achieve independence in their daily lives. Objective: The aim of this study was to explore the knowledge and experience of lower limb amputees regarding physiotherapy rehabilitation at the NAPO institution. Method: The study employed a descriptive cross-sectional design involving 81 participants at NAPO. Data collection was carried out using a questionnaire comprising 29 questions. Data analysis was conducted using Microsoft Excel. All ethical considerations were thoroughly upheld. Results: A total of 74.1% of participants had diabetes mellitus, which was the main cause of amputation. Transtibial amputation was performed in 65.4% of the study population. For 44.4% of participants, the rehabilitation program started 6–12 months after surgery. A total of 88.9% of respondents did not perform any form of exercise before amputation surgery. Additionally, 65.4% of participants did not perform any self-management of their lower limb amputation scar at home. A total of 59.3% of participants perceived physiotherapy rehabilitation at NAPO as more effective than physiotherapy rehabilitation at home. Conclusion: The multidisciplinary rehabilitation program implemented at NAPO for lower limb amputees has proven to be highly effective. However, greater emphasis should be placed on pre-amputation rehabilitation, delayed post-amputation physiotherapy rehabilitation, addressing patients' psychological well-being, and providing education on home care and exercise routines.